Market Movers: the case of bitcoin in the Covid-19 setting - Penela, Daniela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Bitcoin is a virtual currency that provides a completely decentralized secure alternative to the currencies currently used. Nakamoto, the creator of this cryptocurrency, published an article on an encryption mailing list in 2008 with the title “Bitcoin: A Peer-to-Peer Electronic Cash System”, thus giving the creation of this virtual currency. This study aims to analyze the Bitcoin and what factors can influence its price, in the context of a pandemic. This work will focus on the bitcoin price and on five different factors likely to have an influence on his price, such as: Hash Rate, Mining Difficulty, Volatility Index, Google Search and Transaction Cost. The period for this research ranges from 15/03/2020 to 14/11/2021, a total of 96 weeks, to integrate the covid-19 factor into the study. The results show that the variables fsCoinCirculation and fsTransationCost are both necessary conditions for an increase on the bitcoin price, but for low values of bitcoin price there are no necessary conditions. Additionally, findings suggest that Hash Rate influences the price of bitcoin. Finally, fsVix variable was found to be a variable with an important implication in price, namely, in its volatility.